Does gambling preference level affect occupational fraud behavior?—Evidence from a survey study in China - Shihua Huang; Yizao Chen; Baitong Li (Frontiers in Psychology)
Occupational fraud presents significant economic challenges globally. This study aims to understand the factors contributing to such fraudulent behavior and to develop strategies to mitigate it, focusing on the relationship between gambling preferences and occupational fraud within the framework of the fraud triangle theory, emphasizing the ‘pressure' element. To explore this relationship, the research employed several methods, including reliability and validity tests, correlation analysis, and regression analysis, to strengthen the survey research. The findings indicate that individuals with stronger gambling preferences are more likely to engage in occupational fraud. This relationship is mediated by ego depletion and moderated by psychological capital and superstitious beliefs, which align with theoretical models of cognitive biases. Further analysis reveals that psychological capital and superstitious beliefs play a moderating role through the mediating effect pathway from gambling preferences to ego depletion. The study provides valuable insights for developing effective fraud prevention strategies in corporate governance.